2014
DOI: 10.1016/j.pneurobio.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ubiquitin–proteasome system in brain ischemia: Friend or foe?

Abstract: A B S T R A C TThe ubiquitin-proteasome system (UPS) is a catalytic machinery that targets numerous cellular proteins for degradation, thus being essential to control a wide range of basic cellular processes and cell survival. Degradation of intracellular proteins via the UPS is a tightly regulated process initiated by tagging a target protein with a specific ubiquitin chain. Neurons are particularly vulnerable to any change in protein composition, and therefore the UPS is a key regulator of neuronal physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 314 publications
(389 reference statements)
4
84
0
Order By: Relevance
“…36) Brain ischemia also damages protein degradation pathways, causing the accumulation of ubiquitinated proteins. 37) In this study, we also discovered that Z-ligustilide reduced the accumulation of ubiquitinated proteins induced by both MG132 and OGD-Reoxy and provided the evidence that blocking protein aggregation may be an important mechanism for the protection of Z-ligustilide against OGD-Reoxy induced injury. Importantly, HSP70 induction played a key role during this process.…”
Section: Discussionsupporting
confidence: 54%
“…36) Brain ischemia also damages protein degradation pathways, causing the accumulation of ubiquitinated proteins. 37) In this study, we also discovered that Z-ligustilide reduced the accumulation of ubiquitinated proteins induced by both MG132 and OGD-Reoxy and provided the evidence that blocking protein aggregation may be an important mechanism for the protection of Z-ligustilide against OGD-Reoxy induced injury. Importantly, HSP70 induction played a key role during this process.…”
Section: Discussionsupporting
confidence: 54%
“…The third transcript, BTN3A2, originates from the gene located in the juxta‐telomeric region of the HLA locus and is involved in the adaptive immune response and inhibition of INFγ release. GABBR1 has been associated with proteasome activation and cytoskeleton remodelling, with differential responses to IRI, dependent upon severity of insult (Caldeira, Salazar, Curcio, Canzoniero, & Duarte, 2014). UBD has also previously been implicated in renal pathology, via involvement in inflammatory‐mediated signalling and immune system modulation.…”
Section: Discussionmentioning
confidence: 99%
“…25 Results of experiments in both in vivo and in vitro models of brain ischemia have disclosed an increased level of clustered ubiquitinated proteins that may lead to protein aggregates in neurons of the hippocampal CA1 region and ensuing cell death. 10 It has been suggested that irreversible aggregation of translational complex components, chaperones, and protein folding enzymes following brain ischemia lead to inhibition of translation and subsequent neuron death. 26 Consistent with this view, we detected augmented levels of ubiquitinated proteins after either OGD followed by 24 hr of reperfusion or GBI followed by 3 hr of reperfusion, particularly among high molecular weight protein bands in western blots.…”
Section: Discussionmentioning
confidence: 99%
“…10 Following OGD, ubiquitin content was significantly increased in the hippocampal slices (p = 0.0046), while a trend toward increased ubiquitination in tissue transduced with GFP was not statistically significant (p = 0.0722) ( Figure 5). However, the level of ubiquitinated protein in CHIP-transduced slices was comparable to controls (p = 0.9885).…”
Section: Overexpression Of Chip Attenuates Increased Protein Ubiquitimentioning
confidence: 95%
See 1 more Smart Citation